CALCULATION OF AREA OF CONTACT OF BORING PIPE WITH STAGNANT AREA - Білецький, Ярослав Семенович; Сенюшкович, Микола Володимирович; Білецька, Ірина Ярославівна; Осипчук, Михайло Михайлович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
Regressive dependences of area of contact of boring and weighted boring pipes from stagnant are set by an area from the step of spiral of boring column and height of segment of stagnant area.